Evaluating irrigation and fertilizer strategies for sustainable forage productivity and improved nitrogen efficiency in the sub-humid highlands of Ethiopia - Taye, C.W.; Hussein, Misbah A.; Ayalew, A.D.; Assefa, T.T.; Fohrer, N.; Riga, Fikadu T.; Derseh, Melkamu B.; Adie, Aberra; Tilahun, Seifu A. (Elsevier, 2025)
Livestock productivity in Ethiopia is hampered by the limited quantity and quality of feed, largely due to lack of knowledge on the possibility of irrigating forage with good agronomic practices by the development agents, which are further exacerbated by climate variability and resource constraints. This study investigated the effects of irrigation levels, fertilizer types and rates, and forage varieties on nitrogen productivity and residual soil nitrogen (RSN) in Robit-Bata Kebele, Ethiopia. A 3×3×7 factorial design was used, including three irrigation levels (60, 80, and 100% of total available soil water), three fertilizer rates (organic manure at 30 t ha−1 and urea at 100 and 300 kg ha−1), and seven perennial forages (four grasses and three legumes). Over two years (2021–2022), data on dry matter yield (DMY), nitrogen uptake (NU), nitrogen use efficiency (NUE), RSN, and nitrogen surplus (NS) were collected. Full irrigation (I100) yielded the highest DMY (8.7 t ha−1), NU (131.2 kg ha−1), and NUE (46 kg kg−1), and lowest NS (18.9 kg ha−1), although deficit irrigation (I80) resulted in similar (p>0.05) DMY, NU, NUE, and NS. Napier grass ILRI-16791 with 300 kg ha−1 urea achieved the highest DMY (20.7 tha−1) and NU (259.2 kg ha−1), while 100 kg ha−1 urea maximized NUE (138.8 kg kg−1) and minimized NS (-168.8 kg ha−1). Deficit irrigation (I80) combined with manure and Napier grass ILRI-16791 is recommended for optimal productivity and environmental sustainability. This study provides novel insights into site-specific, climate-responsive nutrient and water management strategies for public development agents to support smallholder forage production systems. Future studies should assess economic feasibility and integrated manure-urea applications to enhance soil health and NUE.